The scoring patterns depending on match conditions of world-class taekwondo athletes: application of association rules - Jeon, M.; Kim, E.; Oh, H.; Moon, W.; Kim, D. (Archives of Budo, 2019)
Background and Study Aim: In sports matches, athletes mostly perform repetitive motions in predetermined spaces. Repetitive motions become different according to the features of teams or athletes, which give direct effect to match results. The aim of this study is knowledge about preferred by world-class taekwondo athletes scoring patterns.